2017
DOI: 10.1055/s-0037-1606616
|View full text |Cite
|
Sign up to set email alerts
|

Talonavicular Coalition as a Cause of Foot Pain

Abstract: Tarsal coalitions have an incidence of 2% and are often underdiagnosed. These are considered to be one of the causes of chronic ankle and foot pain. Among all tarsal coalitions, the talonavicular type represents a rare and uncommon condition. The purpose of this article was to present the case of a 35-year-old male patient with a bilateral talonavicular coalition treated conservatively. A review of the literature was also performed to understand the management of this rare condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
(32 reference statements)
0
3
0
4
Order By: Relevance
“…Other literature reviews have demonstrated that talonavicular coalitions, if symptomatic, can be treated conservatively or with a range of surgical options depending on other foot and ankle abnormalities which may be present [1]. Clinically, neither of our patients was deemed symptomatic from their coalitions.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Other literature reviews have demonstrated that talonavicular coalitions, if symptomatic, can be treated conservatively or with a range of surgical options depending on other foot and ankle abnormalities which may be present [1]. Clinically, neither of our patients was deemed symptomatic from their coalitions.…”
Section: Discussionmentioning
confidence: 70%
“…Talonavicular coalition was first described in 1879 [5]. Both autosomal dominant [5] and autosomal recessive [1] genetic transmission have been proposed based on family histories in different case reports. Perhaps both autosomal recessive and dominant etiologies exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A terapia conservadora é necessariamente considerada de primeira linha, enquanto a cirurgia é realizada em caso de falha [3]. As opções de tratamento para coalizões geralmente começam com métodos não operatórios por pelo menos 6 meses, incluem repouso de exercícios intensos, fisioterapia para alongar o tendão de Aquiles, tratamento para torção de tornozelo, imobilização de curto prazo por 3 a 4 semanas, botas de proteção para caminhada e órteses para suporte do arco e salto medial [6].…”
Section: Discussionunclassified
“…As medidas conservadoras, como paracetamol 1 g e ibuprofeno 600 mg em caso no de dor, fisioterapia (exercícios excêntricos de panturrilha e laserterapia) e órteses Brazilian Journal of Health Review, Curitiba, v.4, n.5, p. 21605-21613 sep./oct. 2021 funcionais para os pés com suporte de arco medial por um período de 12 meses [3]. Em alguns casos, a infiltração localizada de injeções de esteróides pode fornecer alívio [4].…”
Section: Discussionunclassified